(untitled) (Research, Society and Development, 2021)
The purpose of this article is to reflect on the challenges faced by Integrated High School in view of the High School Reform, created by Law No. 13,415/ 2017. Integrated High School is understood by researchers in the field of Work-Education as a possibility of crossing towards a training that surpasses the educational duality in Brazil. This is a bibliographic research whose bases are in the academic production of the researchers referred to, in addition to recent publications about Law No. 13,415 / 2017. The results show that this Law was created in a scenario of the rise of the radical right-wing politics, the deepening of neoliberal politics and the commodification of education. It is concluded that the High School Reform, by imposing Formative Itineraries, reinforces dualism, fragments knowledge, hierarchizes schools and disciplines, and subordinates Professional Education to the demands of capital. In view of this, we consider that the so-called crossing to a formation that integrates work, science, technology and culture is in danger of falling back in the face of the interests of capital and the weakening of democracy.